Counseling on The Impact of Early Marriage at Pasar VI Village Kualanamu - Safitri, Riri (JURNAL PENGMAS KESTRA (JPK), 2023)
Marriage is carried out for each couple who is ready to get married both morally and materially and has a commitment to live together and is mature in terms of age so that later the couple is ready to undergo and be able to overcome all the problems that may occur after marriage, however, there are many cases that occur in society regarding early marriage, where the couple is still under age. One form of effort to prevent early marriage is by providing counseling containing information about the negative impacts of early marriage, especially for women. This information can be conveyed to parties who can take part in reducing the rate of early marriage, such as PKK mothers who have an active role in the village. Therefore, the author conducted outreach about the impact of early marriage to PKK mothers in Pasar VI Kualanamu Village, Beringin District, with the aim being that PKK mothers in the village have knowledge about the impact of early marriage, so that they can contribute to reducing the rate of early marriage. . The method applied in implementing this counseling is the lecture method. This community service is carried out in two stages, namely the counseling stage and the assessment stage. The results of the counseling carried out showed an increase in the percentage achieved in the knowledge of PKK mothers regarding the impact of early marriage after receiving the counseling, so it can be seen that this activity is considered to be able to increase the knowledge of PKK mothers in the village. By increasing knowledge about early marriage, the counseling participants who are PKK mothers who are active in the community every day and deal directly with local residents, are expected to be able to contribute to reducing the rate of early marriage, especially in Pasar VI Kualananamu Village.